(untitled) (Circe de clásicos y modernos, 2025)
This study focuses on the eschatological conceptions of ancient Greece through the analysis of the works of the poet Hesiod. Recognized for his works Theogony and Works and Days, Hesiod presents a vision of the world in which divine justice and cosmic harmony are central elements. The influence that the Homeric tradition has had on his representations is examined, allowing both the convergences and divergences between both perspectives to be highlighted. This approach provides a more detailed understanding of the complex beliefs about the afterlife in ancient Greece, as well as a broader view of human nature and its relationship to the divine within the context of Hesiodic poetry.